Quantitative Characterization for the Micronanopore Structures of Terrestrial Shales with Different Lithofacies Types: A Case Study of the Jurassic Lianggaoshan Formation in the Southeastern Sichuan Basin of the Yangtze Region - Weiwei Liu; Kun Zhang; Qianwen Li; Zhanhai Yu; Sihong Cheng; Jiayi Liu; Pei Liu; Fengli Han; Liangyi Tang; Zhengwei Li; Xuejiao Yuan; Yiming Yang; et al. (Geofluids)
Due to the specificity of the geological background, terrestrial strata are widely distributed in the major hydrocarbon-bearing basins in China. In addition, terrestrial shales are generally featured with high thickness, multiple layers, high TOC content, ideal organic matter types, and moderate thermal evolution, laying a solid material foundation for hydrocarbon generation. However, the quantitative characterization study on their pore structure remains inadequate. In this study, core samples were selected from the Middle Jurassic Lianggaoshan Formation in the southeastern Sichuan Basin of the Upper Yangtze Region for analyses on its TOC content and mineral composition. Besides, experiments including oil washing, the adsorption/desorption of CO2 and nitrogen, and high-pressure mercury pressure experiments were carried out. The pore structure of different petrographic types of terrestrial shales can be accurately and quantitatively characterized with these works. The following conclusions were drawn: for organic-rich mixed shales and organic-rich clay shales, the TOC content is the highest; the pore volume, which is primarily provided by macropores and specific surface area, which is provided by mesopores, was the largest, thus providing more space for shale oil and gas reservation. The pores take on a shape either close to a parallel plate slit or close to or of an ink bottle. For organic-matter-bearing shales, both the pore volume and specific surface area are the second-largest and are provided by the same sized pores with organic-rich mixed shales. Its pores take on a shape approximating either a parallel plate slit or an ink bottle. Organic-matter-bearing mixed shales have the lowest pore volume and specific surface area; its pore volume is primarily provided by macropores, and the specific surface area by mesopores and the shape of the pores are close to an ink bottle.